A Resource and Policy Driven Assessment of the Geothermal Energy Potential Across the Islands of St. Vincent and the Grenadines - Koon Koon, Randy; Shah, Kalim; Ashtine, Masaō; Lewis, Santana (Frontiers in Energy Research, 2021)
The energy security of each Caribbean Community (CARICOM) member state is a key issue specifically addressed based on the energy demands of each nation. St. Vincent and the Grenadines (SVG) has the potential to strengthen its energy sector through the exploitation of immense untapped natural geothermal resources. Currently, SVG is planning to integrate base load power through a 10 Megawatt-electric (MWe) geothermal power plant (GPP1). The paper aims to highlight a detailed resource assessment profile of the renewables across SVG and the projected benefits of the proposed 10 MWe geothermal power potential, such as the positive economic development (displacing 149,000 bbls of crude oil), and the transition to a more climate-sensitive nation (displacing an estimated 0.172 million tCO2e/year). In addition, a volumetric method (Monte Carlo simulations) has been applied to reveal that the geothermal reservoir can sustain a minimum of 31 MWe, 34 MWe and 92 MWe over the lifespan of 25–30 years, for well 1 (SVG01), well 2 (SVG02) and well 3 (SVG03) respectively. Given the findings of the assessment and simulations, several policy approaches are identified as potential means of enhancing geothermal resource development and leveraging the resource for the islands’ sustainable energy demands. These include incentivization for public-private partnerships, information certainty, regulatory processes, and strengthened institutions.